(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Preambolo - 2. Si autem peccaverit in te frater tuus. Un caso di sviluppo esorbitante di un brano scritturale? - 3. Istituzione e metanoia; ovvero della irriducibile individualità del soggetto - 4. Su una ipotesi “diffusa” di episkopé. Dislocazione dell’azione penale a livello collegiale? - 5. (segue) Verso un rinnovamento radicale del processo penale (e non solo). The inquisition as model for a papal or episcopal magistrature exempt from intuitus personae. Towards an alternative to overcome the current crisis of penal and administrative justice ABSTRACT: The purpose of this article is to highlight the remains of absolutism that still permeate the legal codes of the Catholic Church (1917 and 1983), as traceable in and hierarchical relationship existing between the udienza diocesana (diocesian audience) and the udienza pontificia (Papal audience) and the individualistic nature of both. The author highlights dramatic elements of inefficiency and anti-historical prejudice in these institutions, which contrast with the hegemonic collegial ethos that has emerged from Vatican II. In proposing the inquisition as archetypal model for a transversal concentration of the judicial districts of different dioceses - as already implemented since 1938 in regard to judgements of matrimonial annulment - the article supports the overcoming of the limits that canon 1423 imposes on the collegial autonomy of bishops. These limits - the author concludes - can be surmounted only by a gradual recentering a collegial strategy on a recognizable unitary fulcrum of penal jurisdiction and the institutionalization of that “tribunal administrativum” that had been promised by canon 1400, § 2, of the current code, but has remained buried between indolence and oblivion in the Papal Curia.